DEVELOPMENT OF COMMERCIAL ENTERPRISE SECURITY PROGRAM - U. A. Ulasenka; S. L. Prischepa (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
With the continuous development of information technologies the question of effective information security management is becoming increasingly important. This article describes step by step development of the security program that allows effectively manage information risk of the organization. The attention is drawn to the important organizational features that need to be considered when building safety documents for their quality implementation and update.